Optimization of empty container repositioning through coordination among vessels - Yu, Chang (2019)
Container shipping plays an important role in facilitating the transportation of wastes, finished and intermediate products. However, due to trade imbalances, imports and exports cannot match each other in terms of both value and volume. Accumulations of empty containers are found in the developed region while shortages of containers are common in the developing region. Reuse of empty containers through reallocation is believed as environmentally sustainable. However, the repositioning cost is considered to not economical since reposition itself does not associate with any revenue. In order to minimize the costs for empty container repositioning, this report studies the optimization of empty container reposition through coordination among liner vessels. The profit that a vessel can probably generate from delivering an empty container is further measured. This report formulates a mathematical model with two parts. The first part generates the solution of optimal coordination among liner vessels to reposition empty containers. The second part determines the empty container coordination cost which is profit for a vessel to deliver empty containers. In the end, the limitations and future areas of study are discussed.